Thermal properties of low density polyethylene/alumina nanocomposites - Ngu, Jenney Lim Song; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw; Ratnam, Chantara Thevy; Ibrahim, Nor Azowa; Mohamad, Hasmaliza (2009)
Thermoplastic low density polyethylene (LDPE) nanocomposites with alumina as filler were prepared by melt intercalation process followed by compression moulding. Before blend the alumina with LDPE, alumina particles were dispersed by using ultrasonication process. To enhance the interaction between alumina and LDPE, surfactant was used to modify the alumina surface. The melting temperature and crystallinity of nanocomposites were investigated by differential scanning calorimetry (DSC). Thermal stability of the nanocomposites studied by using thermogravitational analysis (TGA).